SNHG1 Inhibits ox-LDL-Induced Inflammatory Response and Apoptosis of HUVECs via Up-Regulating GNAI2 and PCBP1 - Lu, Yuan; Xi, Jue; Zhang, Yao; Chen, Wensu; Zhang, Fengyun; Li, Chenzong; Wang, Zhirong (Frontiers in Pharmacology, 2020)
Dysfunction of human endothelial cells is an important trigger for atherosclerosis. Oxidative low-density lipoprotein (ox-LDL) usually was used to stimulate the dysfunction of human umbilical vein endothelial cells (HUVECs). LncRNA SNHG1 (small nucleolar RNA host gene 1) is a cerebral infarction-associated gene. Present study was designed to investigate the role of SNHG1 in ox-LDL-induced HUVECs. Cell viability was evaluated by CCK-8 and MTT assay. Cell apoptosis was detected by flow cytometry analysis. Cell inflammatory response was evaluated by detecting LDH, IL-6, IL-1β levels. The results revealed that up-regulation of SNHG1 attenuated ox-LDL-induced cell injury and inflammatory response in HUVECs. Next, mechanism assays including RIP assay, luciferase reporter assay and RNA pull down assay, helped us to identify the interaction between miR-556-5 and SNHG1. GNAI2 (G protein subunit alpha i2) and PCBP1 (poly(rC) binding protein 1) were identified as the downstream targets of miR-556-5p. SNHG1 regulated dysfunctions of ox-LDL-induced HUVECs via sponging miR-556-5p and up-regulating GNAI2 and PCBP1. SNHG1 attenuated cell injury and inflammatory response in ox-LDL-induced HUVECs via up-regulating both GNAI2 and PCBP1 at a miR-556-5p dependent way.